Intervention and Migrant Families: Critical Analysis of "Vulnerability" from Professionals [Intervenção E Famílias Migrantes: Análise Crítica Da “Vulnerabilidade” Dos Profissionais] [Intervención Crítico de la «Vulnerabilidad» y Familias Migrantes: Desdeanálisis Los/Las Profesionales] - Magana-Frade, I; Calquin-Donoso, C (Revista Latinoamericana de Ciencias Sociales, 2022)
This paper analyzes the meanings that the notion of vulnerability acquires in social interventions with migrant families in Santiago de Chile in relation to a system that has high levels of xenophobia and racism. Qualitative research was carried out using semi-structured interviews and content analysis in a sample consisting of 10 professionals from the psycho-social field who work with the migrant population in the Metropolitan Region of Chile. The results reveal how the social intervention constructs a notion of a migrant subject strongly associated with vulnerability in which the xenophobic and racist matrix exacerbates the dynamics of exclusion. In addition, negative evaluations are expressed by participants in the study about parental practices, an over-culturalization of their care practices and the verification of subtle forms of control, discipline and normalization of migrant families. © 2022 Women s Health Care. All rights reserved.